Método híbrido de detecção de defeitos em redes de sensores móveis utilizando algoritmo de localização - Martins, Leonardo Guedes da Luz (2012)
The technological advances resulting from electronic systems miniaturization were crucial to the reach of current technology. The microelectronics and studies to reduce power consumption in electronic devices provided that mobile sensor networks become increasingly used. A mobile sensor network is composed of several sensors nodes, which work collaboratively to achieve a certain goal. Each network node has layers and applications for specific purposes, two of the most important algorithms present in most applications in sensor networks are failure detectors and localization algorithms. Failure detectors are algorithms that check faulty nodes in the network by exchanging messages. This algorithm is a fundamental block in distributed applications and fault tolerant. Moreover, the localization algorithm is an alternative to GPS use. Using the content of messages transmitted by nodes, the algorithm computes a location coordinates of the node from a reference point. Several methodologies have been proposed in literature for both algorithms. However, even with functional similarities are not found searches uniting these algorithms in one in order to save resources and improve efficiency in wireless sensor networks. This study proposes a hybrid method in which the failure detector takes advantage of messages sent by localization algorithm to perform its task. This solution optimizes the messages exchange sent by nodes, reducing the transmission of data packets. As result, the solution reduces the power consumption of nodes and improves system performance.